DETERMINAN STUNTING PADA SISWA SD DI KABUPATEN PEKALONGAN - Latif, Rr. Vita Nur; Istiqomah, Nor (Universitas Negeri Semarang in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2017)
Stunting is often referred to as short stature as a manifestation of chronic malnutrition. It is often not realized at the age of five, and realized at primary school age. Prevalence of stunting children in Indonesia at 2007 was 37%, whereas in Pekalongan Regency reached 42,2%. Based on previous study, risk factors related with stunting were family factors, diet, and socioeconomic conditions. This study aimed to analyze the association between genetic factors, intake, socio-demography, CED malnutrition, and anatomical defects with the incidence of stunting among primary school students in Pekalongan Regency. This research was cross sectional. Sampling technique used was proportional random sampling until 93 respondents were collected. Stunting data were collected by anthropometry assessment, while socio-demography data were collected by indepth interview with open ended question to parents. Data were analyzed with chi square test. It showed that the parents’ height (genetic) was significantly associated with stunting (p=0.000). However, socio-demographic (p=0.093), intake (p=0.093), CED malnutrition or head circumference status (p=0.119), and anatomical defects (p=0.133) were not significantly associated with stunting. Parents’ height factors (hereditary) was associated with stunting among primary school students.